The effects of squid-baiting pitfall traps for sampling wētā (Orthoptera) and other ground-dwelling forest invertebrates. Issue 2 (2nd July 2020) - Vergara, O. E.; Nelson, N.; Hartley, S.
ABSTRACT: Pitfall traps are commonly used to sample surface-active invertebrates, although the efficiency of the technique varies among taxa. We investigated how baiting pitfall traps with squid influenced sampling of some ground-dwelling invertebrates in New Zealand forests. The study was conducted across a total of 21 sets of seven lethal pitfall traps established between November 2012 and November 2015 in Aorangi and Remutaka forests. Four non-baited and three squid-baited lethal pitfall traps were established per set and remained active for one night during November/December and three nights during February. Squid-baited pitfall traps caught four times as many ground wētā and three times more cave wētā per unit effort than unbaited traps. Most of the ground wētā were identified as Hemiandrus pallitarsis (Walker, 1869). Carabidae, Scarabaeidae, Staphylinidae, Opiliones, Hymenoptera and Araneae were also more abundant in squid-baited than in unbaited traps. There was little difference in the catches of peripheral pitfall traps versus central pitfall traps, suggesting that 5 m spacing is sufficient to generate independent samples. Exceptions were Araneae and Amphipoda which were both approximately 1.5 times more abundant in central compared to peripheral unbaited traps. The attraction of ground and cave wētā to squid provides some insight into their dietary range. The higher catches obtained with squid-baiting, suggests this may be a useful modification to increase sampling rates, which is valuable where sampling effort is logistically constrained such as on islands or other remote study sites.